2017
DOI: 10.1289/ehp189
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Concentrations of Parabens and Other Antimicrobial Chemicals and Their Association with Couples’ Fecundity

Abstract: Background:Human exposure to parabens and other antimicrobial chemicals is continual and pervasive. The hormone-disrupting properties of these environmental chemicals may adversely affect human reproduction.Objective:We aimed to prospectively assess couples’ urinary concentrations of antimicrobial chemicals in the context of fecundity, measured as time to pregnancy (TTP).Methods:In a prospective cohort of 501 couples, we examined preconception urinary chemical concentrations of parabens, triclosan and triclorc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(77 citation statements)
references
References 65 publications
3
71
1
2
Order By: Relevance
“…Tier 2 included 13 publications. Twelve of those publications (Wolff et al , 2010(Wolff et al , 2015Philippat et al 2012Philippat et al , 2014Watkins et al 2015;Aker et al 2016;Ashley-Martin et al 2016;Buckley et al 2016;Lassen et al 2016;Smarr et al 2017;Geer et al 2017) were based on seven different cohorts assembled in France, Puerto Rico, Denmark, Canada, and various parts of the US. One paper ) presented a case-control study that used incident cases identified among members of a French cohort.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Tier 2 included 13 publications. Twelve of those publications (Wolff et al , 2010(Wolff et al , 2015Philippat et al 2012Philippat et al , 2014Watkins et al 2015;Aker et al 2016;Ashley-Martin et al 2016;Buckley et al 2016;Lassen et al 2016;Smarr et al 2017;Geer et al 2017) were based on seven different cohorts assembled in France, Puerto Rico, Denmark, Canada, and various parts of the US. One paper ) presented a case-control study that used incident cases identified among members of a French cohort.…”
Section: Methodsmentioning
confidence: 99%
“…Of the 43 studies, 24 were conducted in North America (Wolff et al , 2010(Wolff et al , 2015Clayton et al 2011;You et al 2011;Buttke et al 2012;Savage et al 2012Savage et al , 2014Koeppe et al 2013;Lankester et al 2013;Buser et al 2014;Spanier et al 2014;Adgent and Rogan 2015;Li et al 2015;Ihde et al 2015;Shiue 2015aShiue , 2015bVelez et al 2015;Ashley-Martin et al 2016;Buckley et al 2016;Poole et al 2016;Scinicariello and Buser 2016;Smarr et al 2017;Geer et al 2017), two studies in the Caribbean (Watkins et al 2015;Aker et al 2016), 10 studies in Europe (Allmyr et al 2009;Chevrier et al 2012;Philippat et al 2012Philippat et al , 2014Bertelsen et al 2013;Buhl et al 2014;Den Hond et al 2013, 2015Geens et al 2015;Lassen et al 2016), four in Asia (Chen et al 2013;Wang et al 2015;Xue et al 2015;Zhu et al 2016), and three in Australia (Cullinan et al 2012(Cullinan et al , 2015a…”
Section: Overview Of Studiesmentioning
confidence: 99%
See 3 more Smart Citations